Glutathione S-transferase enzyme activity and protein expression in patients with recurrent tonsillitis and idiopathic tonsillar hypertrophy - Aydin, Sedat; Gokhan Demir, Mehmet; Oguztuzun, Serpil; Kilic, Murat; Yilmaz, Can; Dirican, Onur (Biomedical papers, 2019)
Objectives: The palatine tonsil is a significant part of the secondary immune system. Tonsillitis and idiopathic tonsillar hypertrophy (ITH) are the most common pathologies of this component. Although there are studies on their pathogenesis, there is insufficient study of the role of antioxidant agents. Glutathione S-transferase (GST) isozymes contribute to the antioxidation reactions in the tissue via the glutathione pathway. The purpose in this study was to reveal the levels of the GST enzyme activity and protein expression of GSTP1 and GSTA1 isozymes in patients with tonsillitis and tonsil hypertrophy, and to investigate their role in the pathogenesis of these diseases. Materials and Methods: Sixteen patients with recurrent tonsillitis and 5 patients with ITH and were included in the study. Cytosolic extracts were prepared from post-tonsillectomy tissues of both patient groups and GST enzyme activities were measured. Results: The expression of GSTP1 was found to be significantly higher than GSTA1 in tissue samples of patients with ITH and recurrent tonsillitis (P<0.001). Increased GST activity and GSTP1 isozyme expression were shown in patients with recurrent tonsillitis compared to the idiopathic tonsillar hypertrophy study group. There was a positive correlation between the expressions of GSTP1 (P=0.040; r=0.47). Conclusion: Increased GST activity and GSTP1 isozymes were demonstrated histologically in the pathogenesis of ITH and recurrent tonsillitis. We believe that the data of changes in antioxidant capacity, obtained from studies with more extensive and larger samples, would support our findings.
Keywords: glutathione S-transferase; GSTA1; GSTP1; idiopathic tonsillar hypertrophy; recurrent tonsillitis